PEMUDA DAN KOTA SANTRI : Konstruksi Sosial Prilaku Pemuda Kota Pasuruan dalam mengkonsumsi makanan dan minuman halal atau haram Prespektif Peter L Berger dan Thomas Luckman - Dewi Masitah; Hermanto Halil (International Conference on Humanity Education and Society (ICHES), 2023)
The city of Pasuruan is called the city of santri because of the many Islamic boarding schools with various characters, ranging from Salafiyah Islamic boarding schools, economic boarding schools, social pathology pesantren, health pesantren, language and da'wah pesantren, and integrated pesantren. Of all the characters of this complete pesantren, does it have an impact on the behavior of santri and youth around the pesantren to be able to obey Allah by avoiding immorality, eating and drinking unlawful drinks because ideally with the many pesantrens, Pemuda Pasuruan is formed into a society that is educated in Islam and is able to apply values Islamic law. With this phenomenon, researchers are interested in conducting research on the problem of how the social construction of Pasuruan youth in consuming halal or haram food and drinks? This research approach uses a sociological approach and is researched using a qualitative phenomenological method. The theory used as an analytical tool is the social construction theory of Peter L Berger and Thomas Luckman. The results of this study indicate that the youth of Pasuruan City choose between consuming and not consuming illicit goods is a social construction created by the youth themselves as individuals. Pemuda Pasuruan is a human being who is free to determine in a social world that is constructed based on his will. They are not social victims, but as production and reproduction media capable of creating their own social world. Peter L Berger and Thomas Luchman view that the two social construction models that youth created above are inseparable from a dialectical process consisting of three different moments, namely externalization, objectification and internalization.